Paying off a fine by working outside prison: On the origins and diffusion of community service - Faraldo Cabana, Patricia (European journal of criminology, 2020)
Community service is today one of the most significant alternatives to imprisonment, but there is still much discussion and conflicting accounts of its origins, and little is known about the ideology that helped to introduce and spread this criminal justice innovation. Throughout the 19th century, unpaid work without deprivation of liberty was conceived and promoted as a way of paying off fines when offenders’ insolvency precluded payment in money, thus avoiding imprisonment for defaulters. This article intends to highlight these liberal precedents, but also to explain the ideology and mechanisms that helped to spread this criminal justice innovation, taking into account that its diffusion has occurred in different ways, at different times and for varied reasons in each country. The implementation of community work in Europe has not been linear and progressive, but rather has been marked by historical differences that have culminated in varying degrees of success - and relative failure.